Pengaruh Pengaruh Pengeluaran Pemerintah di Bidang Pendidikan, Kesehatan dan Ekonomi Terhadap Tingkat Kesejahteraan Masyarakat di Provinsi Bali - Aditia, Ngakan Made Agung; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 2, Februari 2018 (pp. 212 - 380), 2018)
The problem of social welfare that develops shows that some citizens have not fulfilled their basic needs independently in poverty condition. This study aimed to determine simultaneously and partially the influence of government spending in the field of education, health and economics towards the level of welfare of society in the Province of Bali Year 2010-2015. This study used secondary data, through documentation and multiple linear regression data analysis. The results showed that simultaneously government expenditures in education, health, and economics have significant effect on the level of welfare. Partially, government expenditures of education have positive and significant influence to the welfare. Government health expenditures have a positive and significant impact on the welfare. Government economic expenditure has a positive and significant impact on the welfare level of the people of Bali Province in 2010-2015.